2022
DOI: 10.3389/fphys.2022.938101
|View full text |Cite
|
Sign up to set email alerts
|

Short-pulsed micro-magnetic stimulation of the vagus nerve

Abstract: Vagus nerve stimulation (VNS) is commonly used to treat drug-resistant epilepsy and depression. The therapeutic effect of VNS depends on stimulating the afferent vagal fibers. However, the vagus is a mixed nerve containing afferent and efferent fibers, and the stimulation of cardiac efferent fibers during VNS may produce a rare but severe risk of bradyarrhythmia. This side effect is challenging to mitigate since VNS, via electrical stimulation technology used in clinical practice, requires unique electrode des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…The fact that we were able to observe this frequency-dependent phenomenon experimentally validates the hypothesis that we were activating the sciatic nerve using µMS rather than through electrical stimulation contributed by current leakage from the µcoils; in electrical stimulation, one would expect to observe strong leg movements at higher duration-higher amplitude combinations and weak leg movements at lower duration-higher amplitude combinations. Furthermore, this dose-response relationship further confirms that the frequency-dependent activation of the sciatic nerve cannot be the result of the Joule heating effect from the µcoils [38] (see supplementary information S7). To prevent activation of the sciatic nerve through current leakage at the µcoil connections of the MagPen, a water-tight and biocompatible coating was used to insulate the MagPen.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The fact that we were able to observe this frequency-dependent phenomenon experimentally validates the hypothesis that we were activating the sciatic nerve using µMS rather than through electrical stimulation contributed by current leakage from the µcoils; in electrical stimulation, one would expect to observe strong leg movements at higher duration-higher amplitude combinations and weak leg movements at lower duration-higher amplitude combinations. Furthermore, this dose-response relationship further confirms that the frequency-dependent activation of the sciatic nerve cannot be the result of the Joule heating effect from the µcoils [38] (see supplementary information S7). To prevent activation of the sciatic nerve through current leakage at the µcoil connections of the MagPen, a water-tight and biocompatible coating was used to insulate the MagPen.…”
Section: Discussionsupporting
confidence: 67%
“…ous study by Minusa et al [27] reported a temperature increase of ∼1-1.5 • C in aCSF when the µcoils were driven by the alternating current necessary for neural activation. Recently, Jeong et al [38] used an optical probe to measure the temperature increase in the neural tissue during micromagnetic activation and reported a similar observation. Park et al [41] used FEA techniques to optimize the geometrical parameters of a planar µcoil such that the temperature rise in neural tissues is below 1 • C. We have performed an independent study involving experimental and numerical calculations of the heat energy released from the µcoil.…”
Section: Circuit Characteristics Of the µCoilmentioning
confidence: 73%
See 1 more Smart Citation
“…When compared to monophasic stimulation, biphasic stimulation causes less tissue damage due to the neutralization properties of electrochemical reactions ( Tai et al, 2005 ). The intrinsic biphasic nature of the induced electric field suggests that micro-coil stimulation can lead to a null charge integrated over time, and provide biocompatible stimulation ( Jeong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [41] has recently reported micromagnetic vagus nerve stimulation (μVNS) where the animals were anesthetized using isoflurane as the anesthesia. However, isoflurane has a depressive effect on the peripheral nervous system (PNS), particularly on the baroreflex [22,31].…”
Section: Introductionmentioning
confidence: 99%